A168 PROSPECTIVE EVALUATION OF THE USE OF BIOPSY FORCEPS FOR THE ENDOSCOPIC TREATMENT OF SCHATZKI RINGS. (15th March 2019) - Charette, J H; Curley, M; David, J; Buresi, M c; Gupta, M; Andrews, C N
Abstract: Background: A Schatzki ring is a circumferential fibrotic thickening of the esophageal submucosa located at the gastroesophageal junction (GEJ), which typically presents with dysphagia or food impaction. Current recommendations for the treatment of Schatzki rings are largely anecdotal and lack supporting clinical data. Commonly used procedures for the treatment of Schatzki rings include dilation procedures using bougie or balloon dilators. Unfortunately these techniques are plagued with high recurrence rates (63–89% after 5 years). Despite being a simple and effective alternative, ring disruption using biopsy forceps is a much less frequently employed technique. The functional lumen-imaging probe (endoFLIP) is a commercially available device, which employs impedance planimetry to measure luminal diameters and pressures and reporting as a combined measurement known as the distensibility index (DI). This study utilizes endoFLIP to objectively measure changes in the DI at the GEJ. Pairing endoFLIP with the MDQ30 dysphagia score provides a means of assessing the effectiveness of Schatzki ring disruption using biopsy forceps. Aims: The aim of this study was to demonstrate that both dysphagia and the DI at the GEJ are improved by obliterating Schatzki rings with biopsy forceps and that DI at the GEJ correlates with symptoms of dysphagia in patients with Schatzki rings. Methods: Thirty-five patients with dysphagia were identified as having Schatzki rings on upper GI series in the absence of exclusion criteria. Participants completed the MDQ30 prior to, and 30 days after the procedure. Endoscopies were performed under conscious sedation and using the EndoFLIP catheter, the DI was measured before and after the intervention. Biopsies were collected to assess for the presence of EoE and the ring was obliterated using forceps. All data was analyzed. Results: Of the 35 patients recruited, 7 were found to have either a peptic stricture or no ring. The remaining 26 patients underwent treatment for their Schatzki ring. The distensibility index and MDQ30 scores were evenly distributed and pairwise student t-tests were carried out, comparing pre & post treatment scores. Six patients in the population had endoscopic features suggestive of EoE however only 4 had biopsy confirming EoE. Nine of the patients had reflux esophagitis ranging from LA grade A to C. Student t-tests comparing both the pre and post treatment DI and pre and post MDQ30 scores show statistically significant difference (p=0.01 and p<0.01 respectively). There was no statistically meaningful correlation between MDQ30 and distensibility index (DI) scores. Conclusions: Biopsy forceps disruption of Schatzki rings results in improvement in dysphagia scores and the DI at the GEJ. There was no correlation between the two metrics. Funding Agencies: None